Magnetic Resonance Imaging or Computed Tomography for Suspected Acute Stroke: Association of Admission Image Modality with Acute Recanalization Therapies, Workflow Metrics, and Outcomes. Issue 2 (10th June 2022) - Fischer, Urs; Branca, Mattia; Bonati, Leo H.; Carrera, Emmanuel; Vargas, Maria I.; Platon, Alexandra; Kulcsar, Zsolt; Wegener, Susanne; Luft, Andreas; Seiffge, David J.; Arnold, Marcel; Michel, Patrik; et al.
Abstract : Objective: To examine rates of intravenous thrombolysis (IVT), mechanical thrombectomy (MT), door‐to‐needle (DTN) time, door‐to‐puncture (DTP) time, and functional outcome between patients with admission magnetic resonance imaging (MRI) versus computed tomography (CT). Methods: An observational cohort study of consecutive patients using a target trial design within the nationwide Swiss‐Stroke‐Registry from January 2014 to August 2020 was carried out. Exclusion criteria included MRI contraindications, transferred patients, and unstable or frail patients. Multilevel mixed‐effects logistic regression with multiple imputation was used to calculate adjusted odds ratios with 95% confidence intervals for IVT, MT, DTN, DTP, and good functional outcome (mRS 0–2) at 90 days. Results: Of the 11, 049 patients included (mean [SD] age, 71 [15] years; 4, 811 [44%] women; 69% ischemic stroke, 16% transient ischemic attack, 8% stroke mimics, 6% intracranial hemorrhage), 3, 741 (34%) received MRI and 7, 308 (66%) CT. Patients undergoing MRI had lower National Institutes of Health Stroke Scale (median [interquartile range] 2 [0–6] vs 4 [1–11]), and presented later after symptom onset (150 vs 123 min, p < 0.001). Admission MRI was associated with: lower adjusted odds of IVT (aOR 0.83, 0.73–0.96), but not with MT (aOR 1.11, 0.93–1.34); longer adjusted DTN (+22 min [13–30]), but not with longer DTP times; and higher adjusted odds of favorable outcome (aOR 1.54, 1.30–1.81). Interpretation: We found an association of MRI with lower rates of IVT and a significant delay in DTN, but not in DTP and rates of MT. Given the delays in workflow metrics, prospective trials are required to show that tissue‐based benefits of baseline MRI compensate for the temporal benefits of CT. ANN NEUROL 2022;92:184–194